Malaria: Probably Locally Acquired in Toronto, Ontario. (1st June 1998) - Baqi, Mahin; Gamble, Ken; Keystone, Jay S; Kain, Kevin C
Abstract : Although local acquisition of malaria has been reported in the United States, no such cases have been reported in Canada. The authors report a case of Plasmodium vivax malaria in a patient with no travel to a malarious area in the preceding nine years, and postulate local acquisition as the most likely explanation for her infection. The only other plausible alternative explanation of equal biological interest would be that this case represents the latest relapse of vivax malaria ever reported.